All Days 2013
DOI: 10.4043/24310-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application and Evaluation of a NanoFluid Containing NanoParticles for Asphaltenes Inhibition in Well CPSXL4

Abstract: This paper describes the evaluation of a fluid containing nano-materials with high adsorption capacity for Asphaltenes inhibition in a volatile oil field in Colombia. Asphaltenes precipitation has been identified as one of the most potential damaging mechanism affecting the well productivity in Cupiagua Sur Field. Before this work traditional techniques have been tested in the field for asphaltenes inhibition. The goal of the injection of nano-fluids containing nano-particles of alumina with high surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, new cost-effective and environmentally friendly technologies that enhance heavy oil recovery from unconventional resources with lower operational and capital costs are of paramount importance. To this end, nanotechnologyin the form of nanoparticleshas recently become an area of research interest for the oil industry. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new cost-effective and environmentally friendly technologies that enhance heavy oil recovery from unconventional resources with lower operational and capital costs are of paramount importance. To this end, nanotechnologyin the form of nanoparticleshas recently become an area of research interest for the oil industry. …”
Section: Introductionmentioning
confidence: 99%
“…These experiments can be conducted at high-pressure and high-temperature conditions . They can also be employed to evaluate the effectiveness of different asphaltene inhibitors in mitigating permeability reduction …”
Section: Test Methods For Asphaltene Inhibitorsmentioning
confidence: 99%
“…After eight months of operation tracking, the results showed that the asphaltene content in the produced oil of the well remained stable, and the oil production exceeded the baseline by about 300 barrels/day. By tracking and measuring the concentration of nanoparticles in the production water, it can be concluded that with the increase in operation time, the inhibition process of asphaltene deposition was effective, and the oil production remained above the baseline [ 125 ]. It can be seen that the application of nanotechnology in the Cupiagua Sur oilfield is booming, which confirms that the adsorption of asphaltene molecules by nanoparticles is effective.…”
Section: Field Application Of Nano-asphaltene Deposition Inhibitormentioning
confidence: 99%